From the Soviet to the French Accounting System (History of Czechoslovak Accounting before collapse of communist regime and then before division of Czechoslovakia) - Vladimír Zelenka; Marie Zelenková (European Financial and Accounting Journal, 2013)
In the period between 1953 – 1965 the system of Book-Keeping Evidence of the National-Economic Evidence was used in Czechoslovakia, based strictly on the Soviet model of accounting. This system was replaced in 1966 by Singular System for Economic Information. The content followed the post-war Singular System for Business Accounting, which was heavily influenced by Germanic Accounting System. Singular System of Economic Information and later Singular System for Socio- Economic Information (in its two developmental stages) differed mainly by how to integrated financial accounting system and financial and cost center accounting. After the fall of communism in 1989 and the beginning of economic changes, a slightly modified accounting system from before 1990 is being used. It was only in 1993 that the financial system is replaced by a completely new one, based on French accounting.
Keywords: M41; 650; Accounting History; Czechoslovak Accounting; Socialist Accounting